Cyclometalated IrIII Complexes as Mitochondria‐Targeted Photodynamic Anticancer Agents. Issue 12 (16th January 2017) - Ouyang, Miao; Zeng, Leli; Qiu, Kangqiang; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract : Photodynamic therapy (PDT) is an attractive therapeutic modality with high therapeutic efficacy and less side effects compared with other therapies. Herein, we developed a series of cyclometalated Ir III complexes based on 2, 2′‐biimidazole with different alkyl substitutions (methyl, ethyl, propyl, and butyl). These complexes can efficiently produce singlet oxygen upon light irradiation. In vitro photocytotoxicity towards four cell lines (HeLa, A549, A549R, and LO2) was examined. Ir1 –Ir5 show quick penetration of cells, remarkable mitochondrial accumulation, strong phototoxicity, and they exhibit high selectivity between tumor cells and normal cells. With the highest 1 O2 quantum yields, Ir5 presents the best PDT efficiency with a high phototoxicity index (PI) value (PI = 150) towards HeLa cells. This work provides a valuable avenue to improve the PDT effect by tuning the lipophilicity and other properties with variation of the alkyl substitution on the photosensitizer. In addition, their satisfying PDT effect to a cisplatin‐resistant cell line (A549R) may contribute to the future development of improved chemotherapeutics. Abstract : A series of cyclometalated Ir III complexes based on 2, 2′‐biimidazole with different alkyl substituents were evaluated towards four cell lines as photodynamic therapy (PDT) agents. They exhibit satisfying PDT effects with high phototoxicity index (PI) values and high selectivity between normal cells and cancer cells. The photoinduced cell death follows a mitochondria‐mediated apoptotic pathway.